Study of maternal and foetal outcome in multifetal pregnancy - Nimbalkar, Pranjal Sanjay; Bava, Amarjeet; Nandanwar, Yogeshwar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Development of two or more foetuses simultaneously in the uterus is termed as multifetal pregnancy. Such pregnancies are associated with increased risk for both mother and child, and this risk increases with the number of offspring’s. The incidence of multifetal pregnancies in LTMMC hospital, Sion during study period was 1.7%. The overall increase in prevalence of multifetal births is of concern because the corresponding increase in the rate of preterm birth compromises neonatal survival and increases the risk of lifelong disability. Methods: Descriptive retrospective analysis of 187 twin pregnancies and 4 triplets was done in our hospital from year January to December 2015. Patients were studied for any adverse antenatal outcome, mode of delivery, and pregnancy outcome both maternal and perinatal. Results: In our study 89% patients belonged to age group 21-30 years. 59% cases were booked and attended antenatal clinic on regular basis. Most of patients with twin pregnancy were primigravida (70%). Commonest obstetric complication was preterm labor (18%). Intrauterine death in 3% and intrauterine growth retardation in 24% were detected during the antenatal follow ups. Out of 187+1, 42% delivered by vaginal route whereas 58% patients required Caesarean section. Malpresentation being the commonest indication for caesarean in 50% cases. Conclusions: Risk of pregnancy related complication in twins is definitely more than singleton pregnancy. Early diagnosis, careful monitoring of foetal wellbeing throughout pregnancy, administration of corticosteroids and tocolytics, regular antenatal checkups, adequate rest and institutional delivery having level 3 neonatal back up facilities can improve maternal and perinatal outcome in these patients. Motivating mothers for feeding and taking proper nutrition will help in preventing health problems in babies.